Direct hydrocracking of oxidized bio-oil to hydrocarbons. (15th August 2015) - Tanneru, Sathish K.; Steele, Philip H.
Highlights: Direct hydrocracking of oxidized bio-oil to produce liquid hydrocarbons was tested. Hydrocarbon yield 36.6% higher than for raw bio-oil was achieved. GC–MS results showed 99.2 area% of hydrocarbon compounds in the produced product. The liquid hydrocarbons had 6.9% higher HHV than for HDO of raw bio-oil. Abstract: Hydrodeoxygenation is considered a promising technology to convert bio-oils to liquid transportation fuels. Recently we tested a hydrodeoxygenation method to convert oxidized bio-oil to increase liquid fuel yield, reduce char and reduce required hydrogen. In this current study we tested direct hydrocracking of the oxidized bio-oil to produce high-energy liquid hydrocarbons. We tested various reaction conditions (reaction temperature, hydrogen pressure, time and catalyst type) on the hydrocracking of the oxidized bio-oil. Direct hydrocracking of the oxidized bio-oil produced 36.6% higher hydrocarbons yield compared to direct hydrocracking of the raw bio-oil. The hydrocarbons mixture produced had a higher heating value (HHV) of 43.6 MJ/kg. The oxygen content and acid value were 0.5 wt% and 0.3 mg KOH/g, respectively. Density and viscosity were considerably low at 0.9 g/ml and 1.8 cSt, respectively. pH value was 8.4. The hydrocarbon mixture was also analyzed by GC–MS, FTIR, NMR and DHA.